Jornal mural: educomunicação socioambiental no ensino fundamental - Cardozo, Bruna Santos [UNESP]; Queiroz, Thayline Vieira [UNESP]; Rocha, Bianca Oliveira [UNESP]; Dornfeld, Carolina Buso [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Bulletin Board is one of the environmental educational communication tools, which is an excellent feature in group work. Work on Educommunication associated with Environmental Education are very important, however, there are few studies in this area yet. This study aimed to analyze the possible contributions that the development Bulletin Board offer to the school community. The study was conducted with students from the 6th grade of elementary school of a private school in the city of Ilha Solteira (SP), through extracurricular activities in a project called “Biology Beyond the Island” and developed in partnership with the PROEX-UNESP. We were performed sixteen meetings, during which were discussed topics on environmental issues and proposed different activities, which resulted in material to compose the Bulletin Board. The topics covered were: Scientific Curiosity, Environmental Education, Comments and Opinions, Entertainment, Interviews and Illustrations. According to the data obtained in the meetings, the preparation of the Bulletin Board can contribute positively to the reflections on environmental issues. Both students involved in its production, as the school community can benefit.

O jornal mural é uma das ferramentas da educomunicação ambiental, sendo este um recurso de excelência no trabalho em grupo. Trabalhos sobre Educomunicação associados à Educação Ambiental são de grande importância, porém, ainda existem poucos estudos nessa área. O presente trabalho teve por objetivo analisar as possíveis contribuições que a elaboração de Jornais Murais oferecem para a comunidade escolar. O trabalho foi desenvolvido com os alunos do 6º ano do ensino fundamental de uma escola privada situada na cidade de Ilha Solteira (SP), por meio de atividades realizadas em um projeto extraclasse denominado Biologia Muito Além da Ilha e desenvolvido em parceria com a Pró-reitoria de Extensão Universitária da UNESP. Realizou-se dezesseis encontros, durante os quais foram abordados tópicos sobre questões ambientais e propostas atividades diferenciadas, as quais resultaram em materiais para compor o Jornal Mural. Os tópicos trabalhados no jornal mural foram: Curiosidade Científica, Educação Ambiental, Comentários e opiniões, Entretenimento, Entrevistas e Ilustrações. De acordo com os dados obtidos nos encontros, a elaboração do Jornal Mural pode contribuir de forma positiva promovendo reflexões sobre a problemática ambiental. Tanto os alunos envolvidos com a sua confecção quanto os alunos leitores e a comunidade escolar podem ser beneficiados.
Keywords: Bulletin board; Environment education; Educommunication; Jornal mural; Meio ambiente; Educomunicação